PENEGAKAN HUKUM PELANGGARAN LALU LINTAS TERHADAP PENGEMUDI SEPEDA MOTOR BERDASARKAN UNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN DI WILAYAH HUKUM KEPOLISIAN SEKTOR KANDIS - Gunawan Januar S; Erdianto '; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Under Indonesian law has very clearly set on traffic behavior, but in fact what is happening today in the field do not match those in the aspired legislation. Based on this fact, there are three formulation of the problem in writing this essay, namely: First What is the enforcement of traffic law violations against the driver of the motorcycle based on Law No. 22 of 2009 on Road Traffic and Road Transport in the jurisdiction of Police Sector ?, second Kandis Any obstacles law enforcement of traffic violations against the motorcycle driver based on Law No. 22 of 2009 on Road Traffic and Road Transport in the jurisdiction of Police Sector ?, Kandis third, How is the effort made by the police in overcoming obstacles law enforcement of traffic violations against the motorcycle driver based on Law No. 22 of 2009 on Road Traffic and Road Transport Sector in the jurisdiction of Police Kandis?The research method in this study is a qualitative research method with empirical juridical or sociological law research. Data sources supported by primary and secondary data sources. Data collection techniques used were interviews, questionnaires and review of the literature. After the data collected then analyzed qualitatively, and draw conclusions with a deductive method of thinking is to analyze the problems of the general form into special shapes. From the results of research and discussion, it can be concluded that, Enforcement hukm against pelanngaran traffic offender is to crack down directly with menilang and hold the perpetrators of wild races of motor vehicles and must follow the court proceedings. Not only is it for offenders who do not have the equipment in the compulsory motor menglengkapinya prior motor vehicle freed. The constraints are the lack of professional law enforcement of local police officers, lack of understanding of the law as well masyarakata minimya public awareness for memetuhi applicable law. Then made several attempts to overcome these obstacles by way pemeberikan legal counseling in high schools performed in the first through high school and to disseminate to the general public, as well as increasing the capacity of the police in the implementation of laws and legislation. Keywords: Law Enforcement Traffic offenses